Topiramate causing type II renal tubular acidosis: A case and review of the mechanism. Issue 4 (18th February 2020) - Chahin, Michael; Oye, Monique; Jadeja, Sonal; Sanders, Kimberly; Reddy, Pramod
Abstract: Topiramate has a wide array of pharmacologic effects, including proximal renal tubular acidosis (RTA). Clinicians must be wary of the possibility for development of somnolence due to compensatory hyperventilation and cardiac dysrhythmias. Abstract : Topiramate has a wide array of pharmacologic effects, including proximal renal tubular acidosis (RTA). Clinicians must be wary of the possibility for development of somnolence due to compensatory hyperventilation and cardiac dysrhythmias.